The goddess and the sun in Indian myth : power, preservation and mirrored Māhātmyas in the Mārkaṇḍeya Purāṇa /: power, preservation and mirrored Māhātmyas in the Mārkaṇḍeya Purāṇa. (2020) - Balkaran, Raj
No abstract available